2022
DOI: 10.3390/medicina58091194
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine Treatment May Improve Clinical Outcome in Patients with COVID-19

Abstract: Background and objectives: The COVID-19 pandemic continues worldwide, and there is no effective treatment to treat it. Chinese medicine is considered the recommended treatment for COVID-19 in China. This study aimed to examine the effectiveness of tetrandrine in treating COVID-19, which is originally derived from Chinese medicine. Materials and Methods: A total of 60 patients, categorized into three types (mild, moderate, severe), from Daye Hospital of Chinese Medicine with a diagnosis of COVID-19 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The Chinese medicinal vine plant Stephania tetranda S. Moore contains a bisbenzylisoquinoline alkaloid named tetrandrine. Recent clinical studies have reported improved outcomes in patients with COVID-19 and those with silicosis when treated with tetrandrine [153,154]. Aside from its calcium-channel-blocking properties, accumulating evidence suggests that it targets cancer-associated inflammation, induces apoptosis, and reverses multidrug-resistant cancer cell lines [155].…”
Section: Alkaloidsmentioning
confidence: 99%
“…The Chinese medicinal vine plant Stephania tetranda S. Moore contains a bisbenzylisoquinoline alkaloid named tetrandrine. Recent clinical studies have reported improved outcomes in patients with COVID-19 and those with silicosis when treated with tetrandrine [153,154]. Aside from its calcium-channel-blocking properties, accumulating evidence suggests that it targets cancer-associated inflammation, induces apoptosis, and reverses multidrug-resistant cancer cell lines [155].…”
Section: Alkaloidsmentioning
confidence: 99%